How do female migration and gender discrimination in social institutions mutually influence each other? - Ferrant, Gaëlle (OECD Development Centre Working Papers, 2015)
Using the Social Institutions and Gender Index (SIGI) from the OECD Development Centre, this paper provides evidence of the two-way relationship between gender inequality in social institutions and South-South migration. Discriminatory social institutions in both origin and destination countries are one additional determinant of female migration. Gender inequality appears to be both a pull and a push factor for migrant women. On one hand, higher gender discrimination at home reduces female emigration, since women's restricted opportunities and low decision-power limit their possibility to move abroad. On the other hand, lower discrimination in the destination country attracts female immigration. However, they have no significant impact on male migration, suggesting that male and female incentives to migrate differ